PENGARUH SOLVABILITAS TERHADAP PERTUMBUHAN LABA PERUSAHAAN ASURANSI SYARIAH DI INDONESIA PERIODE 2011-2018 - Fadli Fadli; Rima Rima (UIN Sultan Maulana Hasanuddin Banten, 2020)
Solvency is the ability of a company to fulfill all its obligations. The obligations referred to here are debts that must be paid. Debt is an obligation that must be paid by a company to another party within a certain period due to transactions that have occurred in the past. The amount of corporate debt is closely related to solvency. From the financial data contained in the table, it can be seen that the solvency on the profit growth of sharia insurance company in Indonesia for the 2011-2018 period have experienced significant developments fluctuatuations. This study was conducted to examine how much influence the solvency on the profit growth of sharia insurance company in Indonesia for the 2011-2018 period. The samples used were 6 sharia General Insurance Companies and sharia units that met the sample criteria. The observation period of this research is from 2011 to 2018. The method used in this study is a quantitative method that uses the quantitative research methods, testing hypotheses using simple linear regression analysis through the test (t). The analysis tool in study uses simple regression analysis that involves one independent variable as a predictor of the value of the dependent variable. The Statistical analysis used was software namely SPSS Version 25.0. the results of this study indicate that a significant effect of the tcount is 1,002 while the ttable values ​​obtained from the t distribution are sought at the significance of 5%: 2 = 2.5% (two-way test) degrees of freedom (df) nk-1 or 48-1 -1 = 46, we get t table of 1.67866. therefore tcount> t table = 1.002> 1.67866 with a significance level of 0.005, it can be concluded that Ho is accepted and Ha is rejected. The influence derived from the coefficient of determination (R-Square) of 0.064 means that the magnitude of the effect of solvency on earnings growth is 6.4% while the remaining 93.6% is explained by other factors not examined in this study.